(untitled) (Journal of the College of Education for Women, 2019)
This paper addresses some of the morphological views of Al-Seraphy in the matter of "altasqeer" (reduction) in his book, "shareh ketab Sibawayh" (the explanation of Sibawayh’s book) linking between them (views of Al-Seraphy) and the data of the morphological theme, in ancient times, and recently. Through balancing between what we have learned from the views of Al-Seraphy and the views of other former linguists and grammarians and latecomers of him. In this research we have linguistically and idiomatically explained the definition of "altasqeer" (reduction), and it’s standard morphological balancing and what has deviated from it, by the examples in both cases; then we has produced the views of the grammarians of that "the definition of "altasqeer" (reduction)", starting from Sibawayh and those who followed or goes against him, passing by Al-Seraphy and ending with those who are latecomers, considering from three models an orbit for the research and considering the views of Al-Seraphy, his arguments and inferences on the trueness of his views, and these models are: " "Tasqeer Ahwa"( the reduction of Ahwa), and the reduction of the triple origin name, which has been added to it three more characters, and the origin of (Ruwaid) before it has been reduced. Then we have outbalanced the views of what we found likely to overcome others by God Allah" to be with us" the Acoustic and standard evidence. We ask